Pelatihan Penulisan Ilmiah Bagi Mahasiswa/Mahasiswi Semester III Jurusan Ilmu Komunikasi Universitas Nusa Cendana - Diah, Sharon Claudia Rambu Podu (Prima Abdika: Jurnal Pengabdian Masyarakat, 2025)
The task of writing papers by students has become part of the learning process at the college level. Writing is an aspect that is required of students, but in reality, they do not understand the right way to write scientifically. This can be seen from the collected papers, where the documents in question only contain scientific materials without being accompanied by credible sources. Based on the results of the Focus Group Discussion, it is known that the students do not understand how to find factual information, accurately making citations and references, and they do not understand the structure of writing. Therefore, a training was created to improve students' writing skills. The training was conducted in 4 (four) meetings held in November 2024. The participants in this training were students of the Communication Science Department, Nusa Cendana University. The training results are that students have been able to write scientifically according to the rules, but there are still some shortcomings, such as being less careful in writing foreign terms, and participants are still limited in developing writing in the background section. The theory used to analyze the findings is The Informative Speech by Devito, where this significant change can occur because the resource person can convey the material informatively. In addition, the material presented is also per the needs of the audience. So that in a short time, students can improve and train their abilities according to the suggestions and learning that have been obtained. In conclusion, scientific writing training is useful in building scientific reading and writing habits for students. Scientific writing training can then be followed up by creating similar training for writing thesis proposals and writing journal articles. In addition, training can be provided in the form of video tutorials to help students with scientific writing in class.